Determinants of indirect financial distress costs: evidence from Malaysia / Norhisam Bulot - Bulot, Norhisam (2018)
The aim of this research is to contribute to the finance theory by providing a quantitative estimate on the size of indirect financial distress costs and its determinants. This thesis is novel and original given the fact that not many studies have been done in the area of indirect financial distress costs and very few similar studies have been done specifically on Malaysia. This study is enriched by providing data analysis using both static and dynamic models of panel data instead of either one as found in many previous studies. In this study, firm level yearly data from the year 2001 to 2011, which includes all firms listed as affected issuers under the requirement of Practice Note 4, Practice Note 17 and Amended Practice Note 17 were used. 199 firms with 955 firm-years observations were examined. Financial distress costs were measured in terms of opportunity costs (OC), changes in operating performance (IAES and IAEA), and changes in capital values (CDS and CDA). Findings from this research suggest that the average FDC found to be 10.53% to 24.62% for OC, -21.44% to -44.29% for IAES, -14.46% to -10.86% for IAEA, -1.45% to 4.63% for CDS and 0.27% to 0.78% for CDA. It is also apparent that the size of FDC varies considerably among sectors and the choice of proxy for indirect financial distress costs. The findings also provide evidence on the existence of both costs and benefits of financial distress. The results of the regressions suggest that lagged dependent variables, investment opportunities, intangible assets, liquid assets and firm size found to have a significant influence on the size of FDC, whereas, there is no statistically significant relationship between time in distress and FDC. Depending on the proxy of indirect costs financial distress, firm size, investment opportunities, lagged dependent variables and intangible assets seem to be the most important variables explaining the FDC. As for leverage, change in investment policy, tangible assets, and expected earnings growth, this research does not provide enough evidence on their significance and concludes that these variables cannot be considered as proper explanatory variables of FDC. The knowledge on the size of indirect financial distress costs and its determinants has important implications for the research on capital structure and bankruptcy prediction among others. First, the finding suggests that OC, CDS and CDA are the best proxies for FDC as they provide the support for the existence of indirect financial distress costs. The use of the other two proxies (IAES and IAEA) will lead to bias as they did not provide the evidence for the existence of financial distress costs. This conclusion is especially important for studies that use indirect financial distress costs as one of their predictors. Therefore, future researchers should exercise care in selecting the proxy for the indirect financial distress costs. Second, it is important to note there is no conclusive evidence on the most optimal number and combination of predictors. The choice of proxy will lead to different conclusion on the types and number of predictors to be included in the model. Therefore, empirical findings for this thesis cannot be generalized to another sample. Third, the finding of this research suggested that the indirect financial distress costs increase and becomes apparent as the firm near financial distress. The information can be used as an early warning indicator that will allow policymakers and regulators (such as Bursa Malaysia) to act and take preventive action in ensuring the quality of listed companies in Malaysia.